2021
DOI: 10.1017/s1431927621000076
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Stem Cells Ameliorate Neuropathic Pain in Rats: A Central Component of Preemptive Analgesia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…46 Exogenous administration of mesenchymal stem cells (MSCs) 1 is also being explored as an alternative therapeutic strategy for neuropathic pain. 6,27,64 We previously demonstrated that intraganglionic or systemic administration of MSCs in rats with single ligature nerve constriction or sciatic nerve crush prevents or resolves mechanical and cold allodynia. 11,41 Since then, the antihyperalgesic and antiallodynic effects of systemic 23,53 or intrathecal 6 administration of MSCs in rats with chronic orofacial pain 23 and mice with sciatic nerve ligation or spared nerve injury (SNI) 6,53 have been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…46 Exogenous administration of mesenchymal stem cells (MSCs) 1 is also being explored as an alternative therapeutic strategy for neuropathic pain. 6,27,64 We previously demonstrated that intraganglionic or systemic administration of MSCs in rats with single ligature nerve constriction or sciatic nerve crush prevents or resolves mechanical and cold allodynia. 11,41 Since then, the antihyperalgesic and antiallodynic effects of systemic 23,53 or intrathecal 6 administration of MSCs in rats with chronic orofacial pain 23 and mice with sciatic nerve ligation or spared nerve injury (SNI) 6,53 have been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 1-2 weeks after nerve injury may be the best time for transplantation. A recent finding was that intravenous transplantation of BM-MSCs 4 days before CCI rat modeling also ameliorated NP (Kotb et al, 2021). This finding may have new implication for the clinical treatment of NP.…”
Section: Discussionmentioning
confidence: 83%
“…The process by which transplanted cells migrate to the site of injury is dubbed homing of cells. This phenomenon is beneficial to the survival of transplanted cells, and the migrated cells provide timely and long-lasting analgesia for pain relief by interacting bidirectionally with the residing cells in a damaged microenvironment via paracrine secretion (Naruse et al, 2011;Franchi et al, 2014;Du et al, 2019;Kotb et al, 2021). The homing behavior of transplanted cells has been well described in many studies, but the definitive mechanisms and regulatory processes of their migration process remain unclear (Deak et al, 2010;Liesveld et al, 2020).…”
Section: Homing Of Transplanted Cellsmentioning
confidence: 99%
“…SCT can potentially alleviate neuropathic pain through anti-inflammatory action, the suppression of central sensitization and the inhibition of glial cell activation [ 200 ]. In numerous studies on animal models, the potential effectiveness of SCT for neuropathic pain has been proven [ 227 , 228 , 229 ]. A clinical trial by Vaquero et al demonstrated that therapy with intrathecally administered mesenchymal stromal cells (MSCs) significantly and progressively decreased neuropathic pain in patients after spinal cord injury ( p < 0.003) [ 199 ].…”
Section: Treatment Strategies For Neuropathic Painmentioning
confidence: 99%